El Hábeas Corpus en los casos de internamiento no consentido en clínicas o centros terapéuticos y el derecho a la libertad. - Quintana Pazmiño, Carlos Javier (2022)
The present investigation entitled "HABEAS CORPUS IN CASES OF NON- CONSENT INTERNMENT IN CLINICS OR THERAPEUTIC CENTERS AND THE RIGHT TO FREEDOM" has originated from the illegal, arbitrary, and illegitimate detention that happens at the time of entering a person with addictions to a health facility for treatment. This investigation aims to describe a violation of proper personal liberty due to the non-consensual internment of the person in the Addictions Clinic. For compliance, the research is developed in two parts: first, through the treatment of the consistent theoretical framework in 3 units called: the first, habeas corpus, the second, rehabilitation treatment, and the third on the right to personal liberty and the non-consensual internment. The methodological design is appropriate to a social, legal investigation through the legal, legal - doctrinal, legal - analytical, and descriptive comparison research method; qualitative research approach; types of bibliographic, basic, and descriptive research; non-experimental research design. Additionally, information has been collected thanks to the research instruments, with which it has been possible to draw conclusions and recommendations according to the problem investigated.